Deep infection rate in primary total knee arthroplasty: a case series from Oman - Osman, Sari Mohamed; Al Badi, Khoula Suwaidan Said; Al Lawati, Ali Abdullah Mohammed (International Journal of Research in Orthopaedics, 2025)
The aim of this report is to assess deep infection rate in total knee arthroplasty (TKA), in a clean theatre, but without using laminar flow. This report is a retrospective case series of TKA conducted in the same hospital and same single operating room, by a single surgeon, to assess the percentage of post operative deep infection, that needed surgical intervention between June 2016 and December 2023. Infection rate was compared to the rate reported in the literature. A total of 430 knee replacements were reviewed, with data obtained from the electronic medical record system. All of these cases were performed under strict vigilance to prevent infection, all were given pre operative prophylactic antibiotics, and all had a surgical drain that was removed at the first post operative day. Prosthetic joint infections (PJI) was defined as a TKA that needed further surgical intervention for a clinical picture and investigations suggestive of deep infection. In this report, four patients out of a total of 430 patients (0.93%), who underwent primary TKA had developed PJIs as defined. Patient’s age ranged from 57 to 71 years (mean 66 years), with three females and one male patient. Two patients underwent staged revision TKA after confirmation of PJI, while other two patients underwent debridement, change of insert, and implant retention. This report has concluded a rate of deep infection that is comparable to the reported rate in the literature, despite that no laminar flow was used in this case series. Using a surgical drain did not seem to increase the infection rate. Two of the infected cases were from bacteria that cannot be surgically acquired, making the surgically acquired rate of infection even lower (0.47%).